Retropubic vs transobturator Argus adjustable male sling: Results from a multicenter study. Issue 3 (3rd March 2020) - Loertzer, Hagen; Huesch, Tanja; Kirschner‐Hermanns, Ruth; Anding, Ralf; Rose, Armin; Brehmer, Bernhard; Naumann, Carsten Maik; Queissert, Fabian; Nyarangi‐Dix, Joanne; Homberg, Roland; Grabbert, Markus; Hofmann, Torben; et al.
Abstract: Aims: To comparatively analyse outcomes after ARGUS classic and ArgusT adjustable male sling implantation in a real‐world setting. Methods: Inclusion criteria encompassed: non‐neurogenic, moderate‐to‐severe stress urinary incontinence (≥2 pads), implantation of an ARGUS classic or ArgusT male sling between 2010 and 2012 in a high‐volume center (>150 previous implantations). Functional outcomes were assessed using daily pad usage, 24‐hour pad testing, and International Consultation on Incontinence (ICIQ‐SF) questionnaires. Continence was defined as zero pads per 24 hours. Complications were graded using Clavien‐Dindo scale. For multivariate analysis, binary logistic regression models were used ( P < .05). Results: A total of 106 patients (n = 74 [ARGUS classic], n = 32 [ArgusT]) from four centers were eligible. Median follow‐up was 44.0 months (24‐64). Patient cohorts were well‐balanced. We observed a statistical trend in favor of ARGUS classic regarding postoperative urine loss based on standardized 24‐hour pad test (71 ± 162 g [ARGUS classic] vs 160 ± 180 g [ArgusT]); P = .066]. Dry rates were 33.3% (ARGUS classic) and 11.8% (ArgusT, P = .114). In multivariable analysis, ArgusT male sling could not be confirmed as an independent predictor of decreased success (OR, 0.587; 95% CI; 0.166‐2.076, P = .408). There were no Clavien IV and V complications. Inguinal pain was significantly higher after ArgusT implantation ( P = .033). Explantation rates were higher for ArgusT compared to ARGUS classic (14.0 vs 23.3%; P = .371). Longer device survival for the ARGUS classic male sling was observed in Kaplan‐Meier analysis ( P = .198). Conclusions: In the largest comparative analysis of ARGUS classic and ArgusT male sling with the longest follow‐up to date, we observed low continence rates with superior functional outcomes and decreased explantation rates after ARGUS classic implantation.